A 4.49nW/Pixel Light-to-Stimulus Duration Converter-Based Retinal Prosthesis Chip - 최동휘; 노현희; 임매순; 지동우 (Institute of Electrical and Electronics Engineers, 2021)
This paper presents a 288-pixel retinal prosthesis (RP) chip implemented in a 0.18 mu m CMOS process. The proposed light-to-stimulus duration converter (LSDC) and biphasic stimulator generate a wide range of retinal stimuli proportional to the incident light intensity at a low supply voltage of 1V. The implemented chip shows 25.5 dB dynamic stimulation range and the state-of-the art low power consumption of 4.49 nW/pixel. Ex-vivo experiments were performed with a mouse retina and patch-clamp recording. The electrical artifact recorded by the patch electrode demonstrates that the proposed chip can generate electrical stimuli that have different pulse durations depending on the light intensity. Correspondingly, the spike counts in a retinal ganglion cell (RGC) were successfully modulated by the brightness of the light stimuli.